Re-examining Explicitation Hypothesis in Translation: A Study of Character Name Repetition in Ten Chinese Versions of - Ruby Ka Yee Hui; Dechao Li (SAGE Open, 2025)
The explicitation hypothesis, which posits that translations tend to provide more explicit information compared with source texts, has been extensively studied as one of the translation universals in corpus-based translation studies. Previous studies have focused on grammatical cohesive devices, with little research into lexical cohesion to examine the explicitation hypothesis, which is also under-investigated within the realm of children’s literature. Comparing 10 Chinese versions of Alice’s Adventures in Wonderland with the English original, this article re-examines the explicitation hypothesis by investigating character name repetition, which belongs to lexical cohesion, through corpus analysis techniques and qualitative analysis. The results indicate that character names occur significantly more often in the Chinese translations than in the English original, supporting the hypothesis. At individual character level, the keyness analysis reveals that only the name Alice has a significant difference, and thus we posit that explicitation is potentially associated with the centrality of the character in a story. Additionally, the qualitative analysis explores the literary and narrative effects of the repeated occurrences of character names. This study contributes by introducing character name repetition as a novel indicator of explicitation and identifying a new variable that influences the degree of explicitation, encapsulated in the newly proposed “character-driven” theory.